ANALISIS PENDEKATAN BALANCED SCORECARD DALAM PENGUKURAN KINERJA BANDARA INTERNASIONAL SULTAN SYARIF KASIM II - ARIF JAYADI, IMAN (Jurnal Akuntansi AKUNESA, 2015)
The aim of this study was to determine the overall performance of the International Airport Sultan Syarif Kasim II after receiving the award. Balanced Scorecard is based on its four perspective, such as financial perspective, customer perspective, internal business processes, learning and growth perspective. The method used in this research is study case with analysis qualitative descriptive. The source of data is from a document of accountability reports, the customers reports and questionnaires.Results from this study indicate that the performance of the International Airport Sultan Syarif Kasim II from a financial perspective produces less stable performance on every year. At the customer's perspective showing the customer is satisfied with the quality of service and lack of good company's ability to attract new customers, the company's internal business process perspective is able to meet customer needs by doing some development after use of the new gates. On employee learning and growth perspective shows that the company's attention in improving the performance of employees able to provide welfare and trainings. Keywords: Balanced Scorecard, Performance Measurement and Affairs Performance Airport